Teaching Anxiety Levels and Coping Strategies of EFL Novice Teachers - Sunubi, Abdul Haris; Rustam, Utari; Fakhruddin, Zulfah; Arqam, Arqam; Tjalla, Maghdalena; Mustary, Emilia; Afiah, Nur (Institut Agama Islam Negeri Palopo, 2023)
Teaching anxiety is feeling powerless and experiencing tension in teaching. A high level of anxiety affects the quality of teaching performance and teachers’ teaching resilience. This study aims to describe teaching anxiety levels and coping strategies of EFL novice teachers in teaching four English skills (listening, speaking, reading and writing). This study employed a descriptive quantitative design. The data were collected by using online surveys. Total sampling was employed, and ten novice teachers of Islamic schools in Sidrap regency, South Sulawesi, completed online questionnaires adapted from DASS 42 and the COPE scale. The data were analysed using descriptive statistics. The findings showed that EFL novice teachers experience severe anxiety in teaching productive skills (speaking 15.5 and writing 15.1) and moderate anxiety in teaching receptive skills (listening 13.8 and reading 14.8).EFL novice teachers used problem focused strategies more than emotion-focused strategies to combat their anxiety.Keywords: Teaching Anxiety; Coping Strategy; EFL Novice Teachers